Development and evaluation of a pocket card to support prescribing by junior doctors in an English hospital. - Reynolds,M; Larsson,E; Hewitt,R; Garfield,S; Franklin,BD (International Journal of Clinical Pharmacy, 2015)
Background Junior doctors do most inpatient prescribing, with a relatively high error rate, and locally had reported finding prescribing very stressful. Objective To develop an intervention to improve Foundation Year 1 (FY1) doctors' experience of prescribing, and evaluate their satisfaction with the intervention and perceptions of its impact. Methods Based on findings of a focus group and questionnaire, we developed a pocket Dose Reference Card ("Dr-Card") for use at the point of prescribing. This summarised common drugs and dosing schedules and was distributed to all new FY1 doctors in a London teaching trust. A post-intervention questionnaire explored satisfaction and perceived impact. Results Focus group participants (n = 12) described feeling anxious and time pressured when prescribing; a quick reference resource for commonly prescribed drug doses was suggested. Responses to the exploratory questionnaire reinforced these findings. Following Dr-Card distribution, the post-intervention questionnaire revealed that 29/38 (76 %) doctors were still using it 2 months after distribution and 38/38 (100 %) would recommend ongoing production. Conclusions FY1 doctors reported feeling stressed and time pressured when prescribing; this was perceived to contribute to error. A pocket card presenting common drugs and doses was well-received, perceived to be useful, and recommended for on-going use.